2022
DOI: 10.1007/s12274-022-4535-8
|View full text |Cite
|
Sign up to set email alerts
|

Localised solid-state nanopore fabrication via controlled breakdown using on-chip electrodes

Abstract: Controlled breakdown has recently emerged as a highly accessible technique to fabricate solid-state nanopores. However, in its most common form, controlled breakdown creates a single nanopore at an arbitrary location in the membrane. Here, we introduce a new strategy whereby breakdown is performed by applying the electric field between an on-chip electrode and an electrolyte solution in contact with the opposite side of the membrane. We demonstrate two advantages of this method. First, we can independently fab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…Moreover, microRNA sequences could be specifically detected based on their unzipping dynamics from a probe strand as determined from the duration of the change in fluorescence signal . This imaging technique has also been used to determine the position and number of nanopores in a solid-state membrane. …”
Section: Optical Nanopore Sensing Strategiesmentioning
confidence: 99%
“…Moreover, microRNA sequences could be specifically detected based on their unzipping dynamics from a probe strand as determined from the duration of the change in fluorescence signal . This imaging technique has also been used to determine the position and number of nanopores in a solid-state membrane. …”
Section: Optical Nanopore Sensing Strategiesmentioning
confidence: 99%
“…Also, the use of controlled dielectric breakdown serves as a versatile approach to fabricate multiple nanopores in situ. 56 An attractive aspect in this case is the direct fabrication of nanopores in microfluidic devices, which can greatly reduce the numbers of fabrication and assembly steps involved in the production process. 57 An alternative approach relies on multibarreled glass nanopipettes that can be independently controlled (Figure 1C), 58,59 allowing for trapping and dynamic manipulation of individual molecules.…”
Section: Arrayed Nanopore Configurationsmentioning
confidence: 99%
“…In addition to pure insulating materials, CBD has demonstrated its ability to generate nanopores in metal-insulating layers [ 120 , 121 ]. This capability provides a new path for integrating nanopores into nanodevices with a solid-state nanopore perfectly aligned with the on-chip electrodes [ 84 ], which is otherwise challenging for traditional approaches of nanopore fabrication.…”
Section: Cbd Nanopore Fabricationmentioning
confidence: 99%
“…Their work provides a fundamental understanding of the mechanism of nanopore formation during CBD, as discussed in Section 2.2 . Fried et al [ 84 ] have also reported a new CBD strategy to fabricate multiple nanopores locally using on-chip electrodes. The nanopores are self-aligned at the position where an on-chip electrode and electrolyte solution are in contact with the opposite side of the membrane.…”
Section: Localized Nanopore Fabrication By Cbdmentioning
confidence: 99%
See 1 more Smart Citation